The becoming of the non-human animals in a post pandemic world - Liebig, Sueli Meira; Lucena, Rafaela Liebig Ramalho (Revista Letras Raras, 2021)
This work aims at bringing an ecocritical look upon the non-human animals taking into consideration their becoming in a post-pandemic world, focusing on anti-speciesism, since most Literature that deal with the relationship between human beings and other species does it under an instrumental perspective, considering human interest and the animal´s value while an object, as for example the preservation of wild animals as elements that belong to the fauna. Here will be pointed out the way how the shared abilities between human and non-human individuals conjoin to the characterization of this personality. As well as the considered ideal of human dignity is necessarily linked to the conceptof existential minimum and the subsequent list of basic rights for its self-preservation, in a post-pandemic future – concurrently and respected the due proportions – it becomes mandatory the comprehension of non-human individuals while equally subjects with rights, with the construction of a proper dignity that as though is derived from human dignity is not interchangeable with it.